ANALISIS DAN PERANCANGAN DATA WAREHOUSE PADA PERUSAHAAN TRAVEL TRANS CITRA BALI - Pratiwi, Citra (JUSS (Jurnal Sains dan Sistem Informasi), 2023)
The development of technology is now more advanced. The development of increasingly advanced technology can help many things that are useful to humans, for example can help to predict something, so humans can prepare everything according to predictions. The development of technology that can help answer these problems is data warehouse. Data warehouse is a system that works by extracting, managing, adjusting, and sending data sources into dimensional data storage. Therefore, this data warehouse system can help predict with the analysis process, so humans can find out historical data from a company. In this study, the company that will be analyzed is Trans Citra Bali Travel Company. With the existence of historical data, it can be seen what transactions are most carried out on travel company. Therefore, it can be predicted that the month with the most transactions, so it can arrange and prepare what car is needed in each month.